Good practice report : innovative Indigenous teaching and learning. - White, Nereda; Frawley, Jack; Anh, Dang Thi Kim (Office for Learning and Teaching, 2013)
Indigenous participation in higher education, both in teaching and in learning, is generally very low. Numerous programs and initiatives have been implemented to facilitate Indigenous student recruitment, participation, retention and completion in higher education in Australia and elsewhere. This review was established to report on good practices in innovative Indigenous learning and teaching in higher education, focusing on 'what works' in Indigenous higher education. The review consists of three major sections. First, it provides a summative evaluation of the good practices and key outcomes for teaching and learning from completed Australian Learning and Teaching Council (ALTC) projects and fellowships (as at February 2013) relating to the topic of Innovative Indigenous learning and teaching in higher education. Second, it presents a review of relevant Australian and international scholarly research and publications on the topic. Drawing on the observations from the review of ALTC projects and relevant literature, the final section, Recommendations, identifies areas in which further work or development is needed. [Overview]